2022
DOI: 10.1002/saj2.20407
|View full text |Cite
|
Sign up to set email alerts
|

Water repellency prediction in high‐organic Greenlandic soils: Comparing vis–NIRS to pedotransfer functions

Abstract: Soil water repellency (SWR) is a common phenomenon across agricultural soils of South Greenland that can negatively affect soil functions. Existing methods to measure SWR as a function of water content (w) are laborious. This study was conducted to compare the potential of visible-near-infrared spectroscopy (vis-NIRS) as an alternative method to pedotransfer functions (PTFs) for predicting four SWR indices in 143 agricultural soils from South Greenland (clay, 0.016-0.172 kg kg -1 ; organic carbon (OC), 0.009-0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…A significant and negative correlation was observed between S W and RI, showing that increasing S W reduced water repellency (Table S9) in agreement with Hosseini et al (2015). Several studies have reported that soil water repellency increases as OM increases (Blaesbjerg et al, 2022;Li et al, 2013). This was not the case in our study as the OM was correlated to S W positively and RI negatively (Table S9).…”
Section: Soil Water Repellencysupporting
confidence: 69%
See 1 more Smart Citation
“…A significant and negative correlation was observed between S W and RI, showing that increasing S W reduced water repellency (Table S9) in agreement with Hosseini et al (2015). Several studies have reported that soil water repellency increases as OM increases (Blaesbjerg et al, 2022;Li et al, 2013). This was not the case in our study as the OM was correlated to S W positively and RI negatively (Table S9).…”
Section: Soil Water Repellencysupporting
confidence: 69%
“…(2015). Several studies have reported that soil water repellency increases as OM increases (Blaesbjerg et al., 2022; Li et al., 2013). This was not the case in our study as the OM was correlated to S W positively and RI negatively (Table S9).…”
Section: Discussionmentioning
confidence: 99%
“…The literature predominately consists of archaeological and geomorphological studies (e.g., Adderley & Simpson, 2006; Jakobsen, 1991; Massa et al., 2012; Schofield et al., 2010). The anticipation of a warmer climate has prompted a renewed interest in these soils, focusing on their nutrient availability (Caviezel et al., 2017), structural development (Pesch et al., 2021), gas diffusion characteristics (Weber et al., 2020), mechanical properties (Pesch et al., 2020), and soil–water repellency (Blaesbjerg et al., 2022; Weber et al., 2021). The soils are generally characterized by a relatively coarse particle size distribution, high organic carbon (OC) contents, and poor structural development (Jakobsen, 1991; Pesch et al., 2021; Weber et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…While the majority of the studies on WR originate from semiarid and Mediterranean climates, it is becoming increasingly evident that WR also occurs in wetter and colder climates (Doerr et al., 2000; Fu et al., 2021; Hermansen et al., 2019; Seaton et al., 2019). A recent study on soils collected across 23 pasture and cultivated fields in South Greenland revealed that 99% of these soils were water repellent, with 98% of the soils being capable of reaching an extremely high degree of WR (surface tension <40.9 mN m −1 ) (Blaesbjerg et al., 2022; Weber et al., 2021). The high prevalence of WR in these subarctic soils was ascribed to a combination of coarse particle size distribution and high OC content (Weber et al., 2021).…”
Section: Introductionmentioning
confidence: 99%